Analysis of Communication, Collaboration, and Computational Thinking Skills of Students in the Computer and Network Engineering Program (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to analyze the communication skills (COM), collaboration skills (COL), and computational thinking (CT) of vocational high school (VHS) students in the computer and network engineering (CNE) program in Kedıri City, as well as to identify aspects that need to be strengthened to improve students readiness for the world of work. Method: This study used a survey method with a descriptive quantitative approach. The research sample consisted of 379 students selected using random sampling techniques. Data were collected through a closed questionnaire with a Likert scale consisting of 31 statements. Data analysis was performed using descriptive statistics to describe the student’s skills levels. Results: The results showed that students COM, COL, and CT skills were generally in the good category, with averages of 27.55, 52.75, and 40.89, respectively. However, at the indicator level, there were still several aspects that needed to be strengthened, namely the ability to convey information with confidence in COM, contribution and work organization in COL, and decomposition and algorithm development in CT. Novelty: This study provides new insights into the state of 21st century skills among VHS students, particularly those in the CNE program in Kediri City, and suggests the importance of strengthening aspects of skills that are still lacking in order to improve the work readiness of VHS students in an increasingly competitive era.